Impairment of hypoxic pulmonary vasoconstriction in acute respiratory distress syndrome. (15th September 2021) - Gierhardt, Mareike; Pak, Oleg; Walmrath, Dieter; Seeger, Werner; Grimminger, Friedrich; Ghofrani, Hossein A.; Weissmann, Norbert; Hecker, Matthias; Sommer, Natascha
Acute respiratory distress syndrome (ARDS) is a serious complication of severe systemic or local pulmonary inflammation, such as caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. ARDS is characterised by diffuse alveolar damage that leads to protein-rich pulmonary oedema, local alveolar hypoventilation and atelectasis. Inadequate perfusion of these areas is the main cause of hypoxaemia in ARDS. High perfusion in relation to ventilation (V/Q<1) and shunting (V/Q=0) is not only caused by impaired hypoxic pulmonary vasoconstriction but also redistribution of perfusion from obstructed lung vessels. Rebalancing the pulmonary vascular tone is a therapeutic challenge. Previous clinical trials on inhaled vasodilators (nitric oxide and prostacyclin) to enhance perfusion to high V/Q areas showed beneficial effects on hypoxaemia but not on mortality. However, specific patient populations with pulmonary hypertension may profit from treatment with inhaled vasodilators. Novel treatment targets to decrease perfusion in low V/Q areas include epoxyeicosatrienoic acids and specific leukotriene receptors. Still, lung protective ventilation and prone positioning are the best available standard of care. This review focuses on disturbed perfusion in ARDS and aims to provide basic scientists and clinicians with an overview of the vascular alterations and mechanisms of V/Q mismatch, current therapeutic strategies, and experimental approaches. Our review provides a detailed overview of mechanisms underlying the V/Q mismatch in ARDS and its contribution to hypoxaemia, and could help to assess the relevance of treatment options currently being discussed for treatment of ARDS in COVID-19 patients https://bit.ly/3gs2Afj